Does integration policy improve labour market, sociocultural and psychological adaptation of asylum-related immigrants? Evidence from Sri Lankans in Switzerland - Marco Pecoraro; Anita Manatschal; Eva G. T. Green; Philippe Wanner (University of Neuchâtel, Institute of Economic Research (IRENE), 2019)
The marked increase of asylum seekers arriving in Western Europe after 2014 has renewed debates on the policy measures countries should put into place to support their integration. Yet, knowledge about the links between integration policy and broader labour market, sociocultural or psychological adjustment in destination countries is still limited. Exploiting a comprehensive integration policy reform in Switzerland, and using survey data from the Health Monitoring of the Swiss Migrant Population, our difference-in-difference analyses reveal substantial policy effects. Provisionally admitted Sri Lankans benefiting from the reform enjoy a higher employment probability (plus 30 percentage points), increased income levels (plus 60 per cent), better language skills and feel less lonely or without a homeland relative to comparable Sri Lankan asylum seekers who did not benefit from the reform. Robustness checks using register data confirm the beneficial policy effect on labour market participation for the whole population of provisionally admitted individuals.
Keywords: 330; Asylum; Integration Policy; Labour Market; Sociocultural adaptation; Psychological Wellbeing; Difference-in-Differences